(untitled) (Journal of Misan Researches, 2020)
In our study, we dealt with the science of the Almighty’s truth in itself and with its creatures. The divine philosophers all believe in divine knowledge, and that the knowledge of God Almighty in itself is an existential science. But their opinions differed about his knowledge of the Almighty about his creatures, some of them said that his knowledge of the foundations through his detailed knowledge in the same way, and some of them said through the union of the sane and the reasonable, and some of them said that his knowledge is through presence, and some of them said that the images drawn are related to his knowledge of the foundations, and some of them Who said the eternal constants, and some of them said fixed objects. However, Mlasadar did not accept all the theories and opinions presented about the divine science, except that he did not reject it completely, but rather sought to take the strengths in it to be used in presenting his belief about the divine science. Through the circle of active methodical discussion that he conducted to the opinions of others, he presented a pure theory free from all weaknesses, and decorated with all that is required for deistic science. It has been proven with the proof that God Almighty has knowledge of himself in the order of himself, which is the eye of the self, and he also has knowledge of his assets in the same rank, which is called knowledge before existence, and this knowledge is gross in the eye of detailed revelations, and the Almighty has a detailed knowledge of what is only himself from the foundations Arranging itself outside of the transcendent self, and this is the post-existence science, and it is an existential science, for the abstracts themselves, and for the material in its abstract forms.